The Prevalence of Cardiac Diseases in a Contemporary Large Cohort of Dutch Elderly Ankylosing Spondylitis Patients—The CARDAS Study - Milad Baniaamam (MDPI AG, 2021)
Objectives: The aim of the present study was to determine the prevalence of specific cardiac manifestations, i.e., conduction disorders, valvular disease and diastolic left ventricular (LV) dysfunction, in a large cross-sectional controlled cohort of elderly ankylosing spondylitis (AS) patients. Methods: This cross-sectional study assessed the prevalence of valvular disease, conduction disorders and LV dysfunction in 193 randomly selected AS patients compared with 74 osteoarthritis (OA) controls aged 50–75 years. Patients underwent conventional and tissue Doppler echocardiography in combination with clinical and laboratory assessments. Multivariate regression analyses were performed to compare the odds of mitral valve regurgitation (MVR) and aortic valve regurgitation (AVR) between AS patients and OA controls. Results: The prevalence of diastolic dysfunction was trivial and comparable in AS patients compared to controls (respectively, 4% and 3%) and had no further clinical relevance. In addition, the prevalence of conduction disturbances was similar in both groups, with little clinical relevance, respectively 23% vs. 24%. The prevalence of AVR was significantly higher in AS patients compared to the controls, respectively 23% (9% trace, 12% mild, 1% moderate, 1% severe, 1% prosthesis) vs. 11%, p = 0.04. After correcting for age, sex and CV risk factors, AS patients had an odds ratio of 4.5 (95% CI 1.1–13.6) for AVR compared to the controls. In contrast, the prevalence values of MVR were similar and mostly not clinically relevant in AS patients and controls, respectively 36% and 32% and p = 0.46. Conclusion: The prevalence of diastolic LV dysfunction and conduction disorders was mostly not clinically relevant, and similar in AS patients and controls. However, AS patients had an up to five times increased odds to develop AVR compared to controls. Therefore, echocardiographic screening of elderly (50–75 years) AS patients should be considered.